Suvorexant: a promising, novel treatment for insomnia - Lee-Iannotti JK (Dove Medical Press, 2016)
Joyce K Lee-Iannotti,1 James M Parish2 1Division of Neurology, Sleep Disorders Center, Banner University Medical Center, Phoenix, AZ, USA; 2Division of Pulmonary Medicine, Center for Sleep Medicine, Mayo Clinic, Phoenix, AZ, USA Abstract: Suvorexant a novel, orexin receptor antagonist was recently approved by the US Food and Drug Administration for the treatment of sleep onset and sleep maintenance insomnia in August 2014. Multiple animal and human studies support the efficacy, safety, and tolerability of suvorexant for patients of various profiles. Current recommendations advocate for a starting dose of 10 mg and a maximum dose of 20 mg, with cautious use in women, obese patients, and patients taking other CYP3A4 inhibitors. More head-to-head studies comparing suvorexant to other sedative-hypnotic therapies are needed to further delineate which patients will benefit the most from this medication over others. Keywords: insomnia, orexin-receptor antagonist, CYP3A4, benzodiazepan receptor antagonist, MK-4305